Islam Menjawab Tantangan SDGS di Indonesia : A Literatur Review - Roberto Abimanyu Baggio; Rahma Rosaliana Saraswati (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2018)
This study aims to analyze how Islam answer the challenge of SDGs in Indonesia . This research uses descriptive qualitative research method, with data collection techniques of literature review. The researches found that Islam guarantees life for every believer in the world and in the hereafter. Islam has a very essential joint of the Qur'an and As-Sunnah. It contains the basic teachings concerning all aspects of human life, which can then be developed in accordance with the minds of each nation, whenever its time, and wherever it is, Islam is always present functionally solve human problems, because nothing which is not contained in it, including answer the challenge of SDGs